Speech Perception as a Cognitive Process (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Speech perception is the key step to cognitive process in language use and the crucial topic in psycholinguistic study. This paper analyzed speech perception from the aspects of structure, process and importance of each stage.